Equine pegiviruses cause persistent infection of bone marrow and are not associated with hepatitis - Tomlinson, Joy E. (PLoS Pathog, 2020)
Pegiviruses frequently cause persistent infection (as defined by >6 months), but unlike most other Flaviviridae members, no apparent clinical disease. Human pegivirus (HPgV, previously GBV-C) is detectable in 1–4% of healthy individuals and another 5–13% are seropositive. Some evidence for infection of bone marrow and spleen exists. Equine pegivirus 1 (EPgV-1) is not linked to disease, whereas another pegivirus, Theiler’s disease-associated virus (TDAV), was identified in an outbreak of acute serum hepatitis (Theiler’s disease) in horses. Although no subsequent reports link TDAV to disease, any association with hepatitis has not been formally examined. Here, we characterized EPgV-1 and TDAV tropism, sequence diversity, persistence and association with liver disease in horses. Among more than 20 tissue types, we consistently detected high viral loads only in serum, bone marrow and spleen, and viral RNA replication was consistently identified in bone marrow. PBMCs and lymph nodes, but not liver, were sporadically positive. To exclude potential effects of co-infecting agents in experimental infections, we constructed full-length consensus cDNA clones; this was enabled by determination of the complete viral genomes, including a novel TDAV 3’ terminus. Clone derived RNA transcripts were used for direct intrasplenic inoculation of healthy horses. This led to productive infection detectable from week 2–3 and persisting beyond the 28 weeks of study. We did not observe any clinical signs of illness or elevation of circulating liver enzymes. The polyprotein consensus sequences did not change, suggesting that both clones were fully functional. To our knowledge, this is the first successful extrahepatic viral RNA launch and the first robust reverse genetics system for a pegivirus. In conclusion, equine pegiviruses are bone marrow tropic, cause persistent infection in horses, and are not associated with hepatitis. Based on these findings, it may be appropriate to rename the group of TDAV and related viruses as EPgV-2.